THE IMPACT OF TOEFLGO APP ON STUDENTS' READING SKILLS - Billah, Muhammad Zufar Kafa; Lestari, Siti; Wahyuni, Sri (Dinamika Bahasa dan Budaya, 2025)
The effect of the TOEFLGo application on the reading proficiency of Grade 12 students at MA Masalikil Huda Tahunan Jepara is investigated in this study. The pretest and posttest results of 46 students who were split into an experimental group (using TOEFLGo) and a control group (using traditional methods) were compared using a quasi-experimental approach. Linear regression and paired sample t-tests were used to analyze the data. The results showed a substantial correlation (R=0.793) between the initial and final scores, and a considerable improvement in posttest scores (average: 73.04) when compared to the pretest (62.4). The results show that TOEFLGo improves reading comprehension, especially for students with high proficiency. Score fluctuation, however, indicates that low-proficiency learners require specialized support. In order to meet each student's unique learning needs, the study suggests incorporating digital resources such as TOEFLGo into English language training. Keywords: digital learning, reading proficiency, English language, quasi-experiment, TOEFLGo